Corporate governance and cash flow as determinants of dividend payout - Nor Hasmadila, Mukhtar (2014)
This study investigates the relationship between corporate governance characteristics and operating cash flow, including control variables (leverage and firm size) with dividend payout on the 100 largest companies listed on Bursa Malaysia’s main board. It examines the roles of board size, CEO duality, individual ownership, managerial ownership, operating cash flow, leverage and firm size in influencing dividend payout performance. In general, the study contributed to the literature on dividend payout theory in Malaysia and supported the existing literature. Hence, the study used data of the 100 largest companies from all sectors are available in Bursa Malaysia but excluded financial sector companies and missing data. Furthermore, this study covered the data in the year 2012 within Bursa Malaysia. This study finds a positive relationship between board size, managerial ownership and operating cash flows. Managerial ownership and operating cash flows are significant, means it is strongly influenced dividend payout. Meanwhile, CEO duality, individual ownership and control variables (leverage and firm size) have a negative relationship with a dividend payout. These findings are consistent with previous studies by (Hafza & Mirza 2010; Zabihi & Ghaleb 2013).